Identidade, cultura e política: os movimentos estudantis na contemporaneidade - Mesquita, Marcos Ribeiro (2006)
The thematic about youth has gained important space and prominence in the last years. Its visibility, in a great part, resumed through media and market, is reinforced by the appearing of new social movements about youth, like the teenagers of the periphery, the alter-globalists and others that are recently showing their vitality. With the appearance of these new actors, classic youth movements are gaining visibility again, between them, the students movement, which came back into the scene, resuming their traditional discourses about politics and education, but still adapting to new student demands and incorporating other guidelines into the field of culture and identity. In this work we intend to study the participation of student militants through the analysis of four groups that express the actual process of movement s diversification. They are: a) classic students movement; b) courses federation; c) groups of gender and d) groups of culture. We still intent to analyse how the students movement is able to reconstruct its collective identity from the conflict and dialogue with these other different groups. For that, we will rely on some concepts like collective identity and social representations that are important tools for our analysis. In this research, we carried out 24 semi structured interviews with militants from each group cited above and we took part in the main forums and meetings. This work was made between 2002 and 2005